Stock de carbono edáfico y aportes de C del mantillo en forestaciones de Pinus de Misiones = Organic carbon soil stock and mulching C aport in Pinus forest of Misiones - Von Wallis, Alejandra (2023)
Soil Organic Carbon (SOC) plays an important role in mitigating climate change. The forest takes C from the environment to generate biomass and with the contributions of the mulch, part of the carbon enters the soil. It is known that the stock of SOC allows to measure soil reserves. The province of Misiones has 31% of its surface covered by forest plantations established largely on red soils with a predominance of Pinus. P. taeda and hybrid present an average SOC stock in the first 30 cm of soil of 61 Mg*ha-1 , 17 % less than the native forest in the area.